Pool Boiling Heat Transfer Performance and Bubble Dynamics from Pin Fin-Modified Surfaces with Geometrical Shape Variation - Pranoto, Indro (MDPI, 2022)
In this paper, an experimental study investigating the effect of the geometrical shape of the circular and rectangular pin fins on the heat transfer performance and the boiling phenomenon is presented. A pool boiling experiment in the HFE-7100 dielectric working fluid under atmospheric pressure was conducted. Boiling curves and boiling heat transfer coefficients of different test cases were plotted to evaluate the heat transfer performance as well as the captured images of the boiling phenomenon on the test samples. Two quantities, flow resistance and wetted perimeter, were calculated to understand the behaviour of the boiling physics due to variation of fin geometrical shape and, hence, their effect on the heat transfer performance. It was found that the cooling performance of the rectangular pin fins was higher than that of the circular pin fins, despite having a slightly higher flow resistance of 4 and 7, respectively. This is believed to be the result of the longer wetted perimeter up to 27, whereby the nucleation site has a higher probability of generating more bubbles in the same boiling surface area. For the tested modified boiling surface with 196 and 144 pin fins, the average heat transfer performances were found to have differences of up to 3.54 and 1.58 times larger, respectively. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.